Investigation of building certification systems in terms of sustainable preservation: the case of Mardin city in Turkey - İzzettin Kutlu; İrem Bekar (Mehran University Research Journal of Engineering and Technology, 2023)
The global threats that arise due to the changing needs as a result of the advancement of technology cause the rapid depletion of natural resources. This situation necessitates studies to protect resources and reduce energy consumption. Recent studies have particularly emphasized the concept of “sustainability”. Today, as a result of the emergence of sustainability in buildings, certification systems have been developed in which the features of buildings are revealed. In this study, 4 certificate systems frequently used in different countries were discussed. First of all, these systems were examined, and their current data were revealed. The study aims to reveal the sustainability of a historical building located in an important historical city in Turkey according to criteria of the determined certification system. For this aim, the Old Government House in Mardin was discussed as a study area. The historical features of the building and plan features were included in the study area. In the findings of the study, the features of the historical building were determined according to the criteria of certification systems. In the evaluation of the features revealed, suggestions were made especially for the use of energy and water. At this point, to use simple renewable energy sources and systems will support the efficient and recycling of water in the building. This situation will contribute to the sustainable use of the faculty to a great extent. As a result, the sustainable preservation of historical buildings can be achieved in the long term by producing its own energy and using recyclable systems.